2022
DOI: 10.1007/s40520-022-02091-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of Andersen–Newman model to assess cataract surgery uptake among older Australian women: findings from the Australian Longitudinal Study on Women’s Health (ALSWH)

Abstract: Introduction Although Cataract Surgery Rate is increasing, the availability of surgery is outstripped by the increasing number of cataract cases as populations age. Aim The study aimed to identify factors associated with cataract surgery uptake in terms of predisposing, enabling, and need factors in very old Australian women. Method This study used ALSWH data included 6229 women aged 79–84 to 85–90 years. Women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…Finally, seven articles were included in the meta-analysis. [12][13][14][15][16][17][18] Table 1 provides an overview of the characteristics of the studies included in this systematic review, such as the first author's name, country, published year, study design, sample size, P-value, and OR. A total of seven articles were identified from several countries including Ghana, Australia, China, Germany, India, and England.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, seven articles were included in the meta-analysis. [12][13][14][15][16][17][18] Table 1 provides an overview of the characteristics of the studies included in this systematic review, such as the first author's name, country, published year, study design, sample size, P-value, and OR. A total of seven articles were identified from several countries including Ghana, Australia, China, Germany, India, and England.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Insurance coverage exhibits a strong correlation with enhanced health-care accessibility and superior health outcomes, enabling individuals with private health insurance to access the services of their preferred surgeons and expedite the surgical process. [13] A study conducted by reported that financial impediments encompass more than mere health insurance aspects, encompassing transportation expenses and government policies about health insurance reimbursement for cataract surgery. These multifaceted factors exert a pronounced influence on the augmentation of cataract surgery rates.…”
Section: Discussionmentioning
confidence: 99%